Chitin Deacetylases: Properties and Applications - Riccardo A.A. Muzzarelli; Yong Zhao; Ro-Dong Park (Marine Drugs, 2010)
Chitin deacetylases, occurring in marine bacteria, several fungi and a few insects, catalyze the deacetylation of chitin, a structural biopolymer found in countless forms of marine life, fungal cell and spore walls as well as insect cuticle and peritrophic matrices. The deacetylases recognize a sequence of four GlcNAc units in the substrate, one of which undergoes deacetylation: the resulting chitosan has a more regular deacetylation pattern than a chitosan treated with hot NaOH. Nevertheless plain chitin is a poor substrate, but glycolated, reprecipitated or depolymerized chitins are good ones. The marine Vibrio sp. colonize the chitin particles and decompose the chitin thanks to the concerted action of chitinases and deacetylases, otherwise they could not tolerate chitosan, a recognized antibacterial biopolymer. In fact, chitosan is used to prevent infections in fishes and crustaceans. Considering that chitin deacetylases play very important roles in the biological attack and defense systems, they may find applications for the biological control of fungal plant pathogens or insect pests in agriculture and for the biocontrol of opportunistic fungal human pathogens.